2020
DOI: 10.1111/aos.14602
|View full text |Cite
|
Sign up to set email alerts
|

XEN® Gel Stent compared to PRESERFLO™ MicroShunt implantation for primary open‐angle glaucoma: two‐year results

Abstract: To evaluate the long-term efficacy and safety of two minimally invasive glaucoma surgery implants with a subconjunctival drainage approach: the XEN45 Gel Stent â (Xen) implant and the PRESERFLO TM MicroShunt (MicroShunt). Methods: Retrospective comparative case series of primary open-angle glaucoma (POAG) patients with at least 6 months of follow-up after a MicroShunt or Xen implantation augmented with mitomycin C. Results: Forty-one eyes of 31 patients underwent Xen implantation, and 41 eyes of 33 patients, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
109
7
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(149 citation statements)
references
References 26 publications
20
109
7
13
Order By: Relevance
“…We found a slightly greater proportion of complete success (62.1% vs 58.0%, respectively) and qualified success (82.8% vs 79.0%, respectively) than that reported by Scheres et al at month 12, although our sample had a higher baseline IOP 12 .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…We found a slightly greater proportion of complete success (62.1% vs 58.0%, respectively) and qualified success (82.8% vs 79.0%, respectively) than that reported by Scheres et al at month 12, although our sample had a higher baseline IOP 12 .…”
Section: Discussioncontrasting
confidence: 76%
“…Similarly, Scheres et al 12 , in a retrospective study, which included 14 eyes who underwent PMS implantation, reported that mean IOP was significantly decreased from 20.1 ± 5.0 mmHg at baseline to 13.3 ± 2.9 at month-12 (mean difference − 6.8 ± 4.1 mmHg, 95% CI − 10.0 to − 3.6 mmHg, p < 0.0001).…”
Section: Discussionmentioning
confidence: 75%
“…The literature search yielded a total of 311 articles of which 19 including 2215 XEN-implant surgeries were included and considered eligible for the meta-analyses ( Figure S1 ) [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Most studies analyzed a mixture of different types of glaucoma and were limited to a follow-up of one year ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The WMD (95% CI; I 2 ) for IOP (in mmHg) was 7.33 (6.90–7.76; 94%), and for IOP-lowering medication, 1.63 (1.51–1.74; 70%) after two-year follow-up. Unfortunately, only four studies evaluated differences in IOP and IOP-lowering medication between XEN-implant as a standalone procedure and as a combined procedure [ 23 , 25 , 28 , 29 ]. Nonetheless, differences were not statistically significant at follow-up ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mitomycin C (MMC) is also used during the implantation. The device redirects the aqueous humor posteriorly, and has been found to be effective at reducing IOP in initial non-comparative studies on glaucoma and ocular hypertensive eyes, with a low rate of complications, both in the short and in the long term [11][12][13][14]. As a result of the moderately invasive nature of the procedure compared to a trabeculectomy or a GDI, as well as the benefit of posterior aqueous humor redirection, the PreserFlo Ò MicroShunt may be a viable surgical option in eyes with a failed trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%